Genetic Deletion of Zebrafish Rab28 Causes Defective Outer Segment Shedding, but Not Retinal Degeneration - Carter, Stephen P.; Moran, Ailís L.; Matallanas, David; McManus, Gavin J.; Blacque, Oliver E.; Kennedy, Breandán N. (Frontiers in Cell and Developmental Biology, 2020)
The photoreceptor outer segment is the canonical example of a modified and highly specialised cilium, with an expanded membrane surface area in the form of discs or lamellae for efficient light detection. Many ciliary proteins are essential for normal photoreceptor function and cilium dysfunction often results in retinal degeneration leading to impaired vision. Herein, we investigate the function and localisation of the ciliary G-protein RAB28 in zebrafish cone photoreceptors. CRISPR-Cas9 generated rab28 mutant zebrafish display significantly reduced shed outer segment material in the RPE at 1 month post fertilisation (mpf), but otherwise normal visual function up to 21 dpf and retinal structure up to 12 mpf. Cone photoreceptor-specific transgenic reporter lines show Rab28 localises almost exclusively to outer segments, independently of GTP/GDP nucleotide binding. Co-immunoprecipitation analysis demonstrates tagged Rab28 interacts with components of the phototransduction cascade, including opsins, phosphodiesterase 6C and guanylate cyclase 2D. Our data shed light on RAB28 function in cones and provide a model for RAB28-associated cone-rod dystrophy.